L'etude comparative des elements merveilleux dans trois epopees africaines: Soundjata ou I'epopee mandingue, Emperor Shaka The Great: a Zulu Epic et Nsongo'a Lianja: I'epopee nationale des Nkundo - Nkaongami, Josue Bosange (Rhodes University, Faculty of Humanities, School of Languages, 2017)
This thesis is a comparative study in Francophone literature which analyses the supernatural factors in three African epics, namely the Sundiata or Mandingo Epic from West Africa by Djibril Tasmir Niane (1960), Emperor Shaka The Great : A Zulu Epic from Southern Africa by Mazisi Kunene (1979), and Nsongo'a Lianja : the National Epic of Nkundo People from Central Africa by Edmond Boelaert (1949). The study analyses similarities and differences between the supernatural figures in these epics and their respective societies using contextual and socio-critical theories. In this thesis it is demonstrated that the presence of supernatural forces is a sine qua non condition for the existence of the epic in the sense that : "the essential mark of the heroic personality in many African folk epics is its reliance on supernatural resources" (Okpewho 1979 : 119). This study shows that in Africa, supernatural forces play vital roles in the society and therefore dominate the African oral epic traditions. Furthermore, the study is significant in the sense that it tries to describe the worldview, especially the religious and cultural beliefs of the particular society or group that produces the epic. The thesis is made up of six chapters. In the first chapter, I outline the study's subject matter, its aims and objectives, its significance, its assumptions and methodology. In the second chapter, I examine the impact of supernatural devices on the lives of the epic heroes Sundiata, Shaka, and Lianja, the predictions and divinations about their births, childhoods, exiles or epic journeys, their ascension to the throne as well as their genealogies and deaths. Such analysis allows one to identify the supernatural factors surrounding each stage of the life of the heroes, and to understand further the importance of supernatural forces in the communities and institutions where the heroes exercise their powers. In the third chapter, I discuss the typology of the supernatural forces in the heroic epics Sundiata, Shaka and Lianja, using Greimas's theory of actants. I divide the characters into protagonists, accessories and opponents. In the fourth chapter, I examine the sources of the supernatural forces prevailing on Sundiata, Shaka, and Lianja. The chapter shows how supernatural agents act on the epic heroes and how these supernatural beings make or mar them in the course of the narratives. In the fifth chapter, I investigate the supernatural factors acting on the heroes' opponents, and in chapter six, I examine the supernatural forces and heroism of the women in the three epics. In the conclusion, I demonstrate that this analysis of supernatural factors enables us not only to appreciate their place and function in the three African epics under study, but also opens a window onto the culture of the Mandingo, Zulu, and Mongo People's : their activities, beliefs, taboos and the rules which organise their respective societies.,This thesis is presented in two parts: French and English.
A comparative analysis of the supernatural forces in three African epics: The Sundiata or Mandingo Epic, Emperor Shaka The Great: a Zulu Epic and Nsongo'a Lianja: the National Epic of the Nkundo People
Keywords: Uncatalogued